Квадратные уравнения1)12-6(x+3)-7x=(x-2)(x+3)2)(2x+10)(x-1)+5(x-2)=2(7+x)3)1+3(2x-4)+(2x-1)(3-2x)=8

Квадратные уравнения 1)12-6(x+3)-7x=(x-2)(x+3) 2)(2x+10)(x-1)+5(x-2)=2(7+x) 3)1+3(2x-4)+(2x-1)(3-2x)=8
Гость
Ответ(ы) на вопрос:
Гость
1)12-6x-18-7x=x²+3x-2x-6 x²+14x=0 x1=0 x2+14=0 x2=-14 2)2x²-2x+10x-10+5x-10-14-2x=0 2x²+11x-34=0 D=11²-4*2*(-34)=121+272=393=√393 x1=(-11+19,82)/2*2=8,82/4 x1=2,205 x2=(-11-19,82)/4=(-30,82)/4 x2=-7,705 3)1+6x-12+(6x-4x²-3+2x)-8=0 6x-11+6x-4x²-3+2x-8=0 -4x²+14x-22=0|*(-2) 2x²-7x+11=0 D=(-11)²-4*2*22=121-168=-47-нет решения так как D<0.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы